Dampak Internet terhadap Perilaku Generasi Muda Islam - Mukhyar Sani (UIN Antasari Banjarmasin, 2017)
The Internet is a worldwide network between computers to communicate from one place to another in different parts of this vast world in which there are various kinds of information, both positive information, as well as negative where all the information that can be accessed via the internet. Interestingly, one communication tool that can be used by the older generation and the younger generation, even though children. Behind the great benefits, he also had something that could make a person's behavior changed from good to bad when for example he was abused by Internet users including the youth of Islam. The emergence of juvenile delinquency such as fights, and various kinds of perversity can be sourced from the misuse of the internet services. In this context, among the youth of Islam needs to be done scantlings that they